2020
DOI: 10.2528/pierc19121806
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Band Mm-Wave Antenna for 5g-Wigig Communication Systems

Abstract: In this paper, we develop a multi-band circularly polarized planar antenna operating at 28 GHz and 60 GHz for 5G and WiGig applications. The antenna is composed of a square slot antenna fed by a proximity coupled microstrip line and loaded by grounded square loop and three tilted angle strips. Grounded square patch introduces resonance at 60 GHz frequency while the strips introduce resonances at 28 GHz. The square slot is designed as a wide-band antenna which can support these two resonances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The work in Abdelatif et al (2020) presents a new multiband rectangular dielectric resonator antenna that consists of a stacked radiator etched with semi-circular slots on the left and right sides of an upper radiator. In addition to this, a microstrip patch antenna with semi-elliptical slots rectangular in shape having similar measurements is designed for comparison.…”
Section: Related Workmentioning
confidence: 99%
“…The work in Abdelatif et al (2020) presents a new multiband rectangular dielectric resonator antenna that consists of a stacked radiator etched with semi-circular slots on the left and right sides of an upper radiator. In addition to this, a microstrip patch antenna with semi-elliptical slots rectangular in shape having similar measurements is designed for comparison.…”
Section: Related Workmentioning
confidence: 99%
“…Because the available bandwidth is substantially bigger than the occupied Extended author information available on the last page of the article frequency of the radio spectrum, it will deliver much higher data rates and wider channels to many users [5]. The studies clarify that the optimum solution for 5G cellular communications is found to be in the mm-wave range between 28 and 38GHz [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-wideband (UWB) communication systems like UWB banded antennas [4]. In [5], multi-band mm-wave antenna to combine 5 G with Wi Gig apps in mobile or tablet applications at 38GHz and 60GHz. In [6], 2×2 MIMO antenna array for 5G applications tri-band is presented.…”
Section: Introductionmentioning
confidence: 99%